2019
DOI: 10.1088/1361-6501/ab16b3
|View full text |Cite
|
Sign up to set email alerts
|

A new method to study evaporation of sessile drop from permeable surfaces

Abstract: Real time monitoring of the mass of an evaporating liquid drop from a real surface by optical methods cannot account for the volume of the drop that gets trapped between asperities. Mass measurement methods do not have high resolution, necessary to account for the small volume of the drop trapped in the pores. This work uses a non resonant mass sensor with a goniometer to simultaneously measure the mass and contact angle of the evaporating drop. Evaporative flux is used as the quantity of comparison across all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…When the droplet includes no surfactant, the CL recedes smoothly and the contact angle is nearly unchanged during evaporation (see the black lines in panels a and b of Figure ). This corresponds to the situation of a CCA evaporation process that has been observed in many previous experimental studies. …”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…When the droplet includes no surfactant, the CL recedes smoothly and the contact angle is nearly unchanged during evaporation (see the black lines in panels a and b of Figure ). This corresponds to the situation of a CCA evaporation process that has been observed in many previous experimental studies. …”
Section: Resultsmentioning
confidence: 55%
“…Two idealized models have been proposed for the shape evolution of an evaporating droplet: constant contact radius (CCR) model (also known as constant contact area model) and constant contact angle (CCA) model. In reality, they are mixed; as the droplet evaporates, the evolution mode changes from CCR to CCA (or vice versa) or both contact angle and contact radius change simultaneously. However, a quantitative theory, which describes such phenomena, is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in such situation, the contact angle often shows quasi-stationary, apparent contact angle θ app . The phenomena has been studied extensively by experiments and simulation [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The drying of droplets of particle suspensions and polymer solutions on substrates can produce rich deposition patterns, [1,2] including coffee-ring, [3,4] mountainlike, [5][6][7] volcanolike, [8,9] and multi-ring patterns. [10] The drying of liquid droplets is a common phenomenon in daily life, and has practical applications such as inkjet printing, [11] pesticide spraying, [12] semiconductor industry production, [13] etc. The dynamics of droplet evaporation therefore has long been of special interest in scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…Evaporating droplets show complex shape evolution modes that the contact radius can increase or decrease with time under different conditions. [14][15][16][17][18][19][20][21] In 1977, Picknett and Bexon [14] reported on the mass and profile evolution of a slowly evaporating liquid (methyl acetoacetate) drop on a polytetrafluoroethylene (PTFE) surface in still air. They distinguished three evaporation modes: constant contact radius (CCR) mode, constant contact angle (CCA) mode, and mixed mode which changes from one to the other at some point or both contact angle and contact radius change simultaneously.…”
Section: Introductionmentioning
confidence: 99%